KONSERVASI STRUKTUR DAN KONSTRUKSI RUMAH VERNAKULAR TERHADAP LINGKUNGAN RAWAN BANJIR DI TENGGARONG - Zakiah Hidayati; Cisyulia Octavia HS (Indonesian Society of Applied Science, 2016)
Kutai vernacular houses are proven to perform better than most modern houses in Tenggarong with respect to climatic change. Its adaptation is a continuing process including necessary changes as a response to social and environmental constraints. Unfortunately, Kutai vernacular houses are not far from becoming extinct due to maintenance issue, flood prone area, lack of awareness among the owner and less local government regulations. The research project aims to make conservation guideline of the Kutai vernacular house. The structure and construction of Kutai vernacular house is most frequently observed. We envisage that the research project will contribute the guidelines of conservation to any stakeholders. In conclusion, conservation guideline is based on available resources